PROTECTIVE FACTORS FOR FEMALE VICTIMS OF DATING VIOLENCE - Abigail Soesana; Andrian Pramadi; NK. Endah Triwijati (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Gender-based violence is a critical issue in Indonesian society. A key structural barrier is unequal gender relations rooted in a deeply paternalistic culture, which tends to position men as superior. Furthermore, this perception is internalized by some submissive women, ultimately leading to domination, exploitation, and violence. Among the most prevalent cases is dating violence, which has increased significantly each year. Currently, dating violence manifests not only as physical abuse but also as verbal abuse. Research indicates that the most devastating impact of such violence is on the victims' psychological well-being. This study aims to provide an overview of the protective factors among female victims of dating violence by identifying the elements that build resilience. A qualitative case study approach was deemed appropriate for this purpose. The study involved two subjects selected through purposive sampling based on established inclusion criteria. Thematic analysis through the coding of verbatim interview transcripts was employed as the data analysis technique. The study yielded six findings, categorized into two main categories and three themes, which are discussed in detail. The study concludes that the protective factors shaping resilience in dating violence victims include both internal and external factors: individual factors, economic/financial factors, and social support.